Script Inscription Khud Palord A Reflection of the Genius of the Pali language of Prince Thammathibet Chaiyachet Suriyawong - poompao, Sathaporn; คล้ายสุวรรณ ณัฐวุฒิ (Journal of MBU Humanities, 2024)
Khmer script inscription Khud Mae Palord is an inscription from the Ayutthaya period built by Prince Thammathibet Chaiyachet Suriyawong to explain how to combine letters in Pali with Thai Khmer letters for monks and novices who do not have basic knowledge of the Pali language for monks and novices who do not have basic knowledge of the Pali language using an easy-to-understand explanation method That is, explains how to combine letters (vowels, consonants, spellings, following letters) with an 8-row grid, both vertical and horizontal Therefore helping the students to see a clear picture. and learn quickly It is also a display of His Majesty’s genius The Pali language of Prince Thammathibet Chaiyachet Suriyawong said He was proficient in the Pali language and had a deep knowledge of the Pali language.